PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP STOCK PRICE PADA INDUSTRI MANUFAKTUR - HAKIM, MOHAMAD ZULMAN; EKSANDY, ARRY (COMPETITIVE, 2018)
The purpose of this study is to prove empirically the influence of liquidity, leverage and profitability in manufacturing industries listed on the Indonesia Stock Exchange period 2012-2016. The population in this study uses the manufacturing industry. The sampling technique used purposive sampling technique. Based on the predetermined criteria, the sample of 61 companies is obtained. The type of data used in this study is secondary data using panel data regression analysis method (E-Views 9.0). The results of this study indicate that the Current Ratio (CR) has no effect on Stock Price, Debt to Equity Ratio (DER) has no effect on Stock Price and Return on Equity (ROE) have a positive effect on Stock Price.Â  Keywords: Liquidity, Leverage, Profitability and Stock Price